Brainstorming Brainstorming as a Method to Increase students’ Critical Thinking Skill - Yusria Yusria; Eksa Budiarta (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2018)
The reseach discusses about Brainstorming as method to improve the ability of critical thinking for student. The purpose of this research was to improve of critical thinking ability for students on science subject human organ material in class fifth grade at the state Elementary School 111 Sungai Abang VII Koto district of Tebo through brainstorming method. This research method was besed on Classroom Action Researchof Kemmis and Mc. Taggart.. The data obtained through observation, interview, documentation, and evaluation. Data analysis used data display, and conclusion or verification. Results of this research are showed on increasedstudent`s ability of criticl thinking through Brainstorming method in teaching and learning process. The evident could be measured from the evaluation of cycle I and cycle II with the average value in cycle I 68.89 and cycle II 76.12. For the level of completeness in cycle I 55.56% while in cycle II 83.34%. The findings that ability of critical thinkingwas could increased through brainstorming method on class fifth grade at The State Elementary School 111 Sungai Abang VII koto district of Tebo,has achieved of learning and this research couldn`t be generalized.